2018
DOI: 10.3847/1538-4357/aadcfe
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Variability of Two Dusty White Dwarfs

Abstract: The most heavily polluted white dwarfs often show excess infrared radiation from circumstellar dust disks, which are modeled as a result of tidal disruption of extrasolar minor planets. Interaction of dust, gas, and disintegrating objects can all contribute to the dynamical evolution of these dust disks. Here, we report on two infrared variable dusty white dwarfs, SDSS J1228+1040 and G29-38. For SDSS J1228+1040, compared to the first measurements in 2007, the IRAC [3.6] and [4.5] fluxes decreased by 20% by 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 77 publications
1
41
1
Order By: Relevance
“…The Spitzer images for WD J0347+1624 and WD J2100 +2122 show that the targets are clear of nearby contaminating sources, and large-aperture photometry of the IRAC Ch 1 and Ch 2 images does not resolve the discrepancy between the AllWISE and Spitzer photometry. Recently, infrared variability of dusty debris disks around white dwarfs has been detected on timescales of months and years (Farihi et al 2018b;Xu et al 2018;Swan et al 2019b;Wang et al 2019). Intrinsic variability remains a plausible explanation for these two targets and presents some issues for our attempts to fit or describe the infrared excess, as the spectral energy distributions presented in Figure 3 include survey data with epochs spanning several years.…”
Section: Establishing the Infrared Excessmentioning
confidence: 99%
“…The Spitzer images for WD J0347+1624 and WD J2100 +2122 show that the targets are clear of nearby contaminating sources, and large-aperture photometry of the IRAC Ch 1 and Ch 2 images does not resolve the discrepancy between the AllWISE and Spitzer photometry. Recently, infrared variability of dusty debris disks around white dwarfs has been detected on timescales of months and years (Farihi et al 2018b;Xu et al 2018;Swan et al 2019b;Wang et al 2019). Intrinsic variability remains a plausible explanation for these two targets and presents some issues for our attempts to fit or describe the infrared excess, as the spectral energy distributions presented in Figure 3 include survey data with epochs spanning several years.…”
Section: Establishing the Infrared Excessmentioning
confidence: 99%
“…The origin of these gaseous components is uncertain, but current mechanisms include: runaway sublimation of dust at the inner edge of the debris disc due to angular momentum conservation (Rafikov 2011;Metzger et al 2012), a collisional cascade of rocky bodies being ground down into dust and gas (Kenyon & Bromley 2017a,b), collisions produced via a tidal stream of planetary debris impacting on a pre-existing disc (Jura 2008;Malamud et al 2021), and a disc-embedded planetesimal that survived the tidal disruption process, inducing the production of gas through collisions or sublimation (Manser et al 2019;Trevascus et al 2021). Recent observations show that variability of the infrared excess from debris discs is common (Xu & Jura 2014;Xu et al 2018;Swan et al 2019;Wang et al 2019), and it has been proposed that the observed variations are due to the production and destruction of dust via planetesimal collisions which could also produce observable gaseous material (Farihi et al 2018;Swan et al 2021). This is further corroborated by the discovery that debris discs with a gaseous component in emission appear to show the largest amounts of infrared variability (Swan et al 2020), indicating they are the most dynamically active white dwarf debris discs.…”
Section: Introductionmentioning
confidence: 99%
“…There are a handful of objects in the literature with previous detections of a change in their dusty emission, as discussed in Section 3.3. For WD J0959−0200, Xu & Jura (2014) found a drop in K band flux from 57 µJy to 46 µJy which is equivalent to a peak-to-peak drop of 18.5%, and Xu et al (2018b) found a K band peak-to-peak drop of 13% for WD 1226+110. We note the difficulty in comparing the peak-to-peak variability quoted for these objects with the median variability quoted in this work.…”
Section: Expected Variabilitymentioning
confidence: 98%